(untitled) (MAUSAM, 1983)
Rainfall condition in Bangladesh is or seasonal type having maximum monsoonal rain during June-September. During other months of the year the rainfall intensity decreases substantially. In this paper efforts have been made to Investigate Into the occurrence or monthly and annual aridity and drought conditions of Bangladesh. Towards this end, rainfall and temperature data for 31 years (1949-1979) have been collected and processed. “Aridity Index" and ’Drought Index" have been used in this study. It is found that aridity condition generally exists over almost all parts of Bangladesh during November-March while the same prevails a bit longer period, i.e., upto April for the northwestern and western parts of Bangladesh. Drought condition is just irregular and spatially limited meteorological phenomenon in Bangladesh.